OPTIMASI MESIN PULPER SILINDER GANDA (PUL-1K) TERHADAP KUALITAS PENGUPASAN KOPI DENGAN METODE BOX BEHNKEN DESIGN - Ali, Muhammad Mukti; Hermawan, Yuni; Jatisukamto, Gaguk; Darsin, Mahros; ,, Sumarji; Hardiatama, Intan (Jurusan Teknik Mesin, 2023)
The expansion of plantation area increased by 74.33% with a growth rate of 1.61%, in 1980 the area of coffee plantation area was 707,464 ha, while in 2016 the area was 1,233,294 ha. The majority of the coffee cherries produced are robusta coffee cherries and grow at an altitude of 400-700 m above sea level with a temperature of 21-24ºC. A wet coffee berry skin peeler is used to separate the coffee fruit skin, the stripping quality results depend on the use of shaft rotation and the gaps of the peelers, and the gaps of the hoppers. Experimental testing method using the Behnken box design method using shaft rotation of 300 rpm, 400 rpm, and 500 rpm, gaps of the peelers 3 mm, 4 mm, and 5 mm, and 5 cm, 7 cm, and 9 cm of hopper gaps. The gaps of the hoppers has the greatest impact on the results of stripping quality with the smallest P-Value of 0.001 and the largest T-Value of -6.66. The best stripping quality results were obtained in the 6th experiment with shaft rotation of 400 rpm, 3 mm gaps of the peelers, and 5 cm hopper spacing with a stripping value of 87.5%. The predicted variant of the shaft rotation factor is 382.828 rpm, the gaps of the peelers is 3 mm, and the gaps of the hoppers is 5 cm. It is predicted that the results of the stripping quality will reach 88.16%